Prevalence and associated factors of smoking among chinese adolescents: a school-based cross-sectional study - Bingliang Lin; Xin Liu; Wenlong Lu; Xiaobing Wu; Yanyan Li; Ziyang Zhang; Rongyin Fu; Luge Zhang; Jingfan Xiong (BMC, 2023)
Abstract Background Shenzhen has made great efforts to address the tobacco epidemic in the past decade. This study aims to evaluate the current status of the tobacco epidemic among adolescent in Shenzhen, China. Methods The multi-stage random cluster sampling method was used in the school-based cross-sectional study in 2019 and a total of 7,423 junior and high school (both senior and vocational) students were recruited. Information on cigarette use was collected by the electronic questionnaire. Logistic regression analysis was used to examine the associations between current cigarette use and associated factors. ORs with their 95% CIs were reported. Results The prevalence of current cigarette use among adolescents was 2.3%, with boys (3.4%) significantly higher than girls (1.0%). Smoking rates in junior high schools, senior high schools, and vocational senior high schools were 1.0%, 2.7%, and 4.1%, respectively. The results of multivariate logistic regression analysis indicated that gender, age, parental smoking, teachers smoking in schools, friends smoking, exposure to tobacco marketing, and misconceptions about cigarette use were associated factors for adolescent smoking behaviour. Conclusions The prevalence of current smoking was relatively low among adolescent in Shenzhen, China. Personal characteristics, family, and school were associated with current adolescent smokers.